Evolution of Mass Public Buildings and Complexes Problems of Modern Spatial Organization in Bukhara - Ruziev Khoshim Ruzievich; Khaitov Sunnatjon Istamovich; Togboyev Khushnud Iskandarovich (International Journal on Integrated Education, 2022)
The article presents the results of theoretical research - the definition of the main trends and architectural techniques that underlie the construction of the public space of modern shopping complexes in Bukhara and the development of recommendations for their practical implementation.